2016
DOI: 10.1177/2158244016665890
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability in Higher Education

Abstract: Sustainability describes how a system remains diverse and productive; this is the potential for long-term maintenance of well-being having ecological, economic, political, and cultural dimensions. Education for sustainable development (ESD) emphasizes on including the key sustainable development issues into teaching and learning, that is, climate change, disaster risk reduction, biodiversity, poverty reduction, and sustainable consumption. This effort requires effective pedagogy to ensure a participatory teach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
38
1
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 6 publications
2
38
1
5
Order By: Relevance
“…The studies that are available on ESD in Malaysian higher education institutions concentrate on assessing the level awareness of the undergraduates towards SD that were conducted in studies by Zainordin et al (2017) and Wee (2017). Moreover, Reza (2016) has mentioned that although the current ESD in Malaysia has developed the students' knowledge and responsibilities toward sustainability, this has not been verified in any studies. Thus, with this motivation, we are going to gauge the level of perception and attitude towards sustainability among Malaysian undergraduates.…”
Section: Introductionmentioning
confidence: 99%
“…The studies that are available on ESD in Malaysian higher education institutions concentrate on assessing the level awareness of the undergraduates towards SD that were conducted in studies by Zainordin et al (2017) and Wee (2017). Moreover, Reza (2016) has mentioned that although the current ESD in Malaysia has developed the students' knowledge and responsibilities toward sustainability, this has not been verified in any studies. Thus, with this motivation, we are going to gauge the level of perception and attitude towards sustainability among Malaysian undergraduates.…”
Section: Introductionmentioning
confidence: 99%
“…ESD focuses on incorporating sustainable development issues in the teaching and learning process. It aims to motivate future leaders to ensure sustainability in their business and activities (Reza, 2016). Another way of defining ESD is the inclusion of economic, social and environmental dimensions of sustainability in the teaching content, showing that sustainability problems are connected to the society and to human actions (Sawitri, 2017).…”
Section: Higher Education For Sustainable Developmentmentioning
confidence: 99%
“…Thus, when developing the 21 st century leaders, there is a huge demand for the university to nurture young minds to become holistic self (Gelen, 2018;Ithnin, Sahib, Eng, Sidek, & Harun, 2018;Kumar & Al-Samarraie, 2018;Lee, 2017). Reza (2016), Ithnin et al (2018), Zakariya (2014) and Fahimirad, Idris and Kotamjani (2016) strongly emphasized the need to produce excellent academic leaders with the right blend of knowledge, skills, and attitudes to drive higher education in the right direction to bring sustainable development to any country.…”
Section: Introductionmentioning
confidence: 99%
“…More specifically, literature on leadership revealed that students from higher education institutions lacked of effective leadership qualities (Lange, 2015;Le, 2016;Mendenhall et al, 2017;Neeley, Clyne, & Resnick-Ault, 2017;Park, Jeong, Jang, Yoon, & Lim, 2018;Skarbaliene, 2018). It is then suggested that human characteristics can be modified through training (Hassanzadeh, Silong, Asmuni, & Abd Wahat, 2015;Mendenhall et al, 2017;Reza, 2016). Therefore, to inculcate university students with effective leadership qualities, they should be trained with the right knowledge, skills and abilities, and other characteristics.…”
Section: Introductionmentioning
confidence: 99%